Data from: Size‐dependent stress response in juvenile Arctic charr (Salvelinus alpinus) under prolonged predator conditioning ... - Kortet, Raine; Laakkonen, Mika V.M.; Tikkanen, Jouni; Vainikka, Anssi; Hirvonen, Heikki (Dryad, 2019)
Predator conditioning can be used to improve post-release antipredator recognition of hatchery-reared salmonids. However, possible negative stress-related effects of prolonged predator conditioning on juvenile fish physiology are poorly understood. We studied the effects of prolonged (91 days) predator odour exposure on whole-body cortisol level and spleen size in six full-sib families of juvenile hatchery-bred Arctic charr (Salvelinus alpinus). Chemical cues from water containing charr-fed pikeperch (Sander lucioperca) were used as the predator exposure stimuli, and lakewater was used as a chemical control. Our study revealed that juvenile body cortisol levels post-predator conditioning were affected by treatment, fish size and their interaction. Importantly, among the smaller (i.e. slowest growing) charr, the predator-exposed fish had higher cortisol levels than control fish, while the opposite pattern was true for the larger fish. These results suggest that chemical cues from charr-fed predators induce a ... : Arctic_charr_cortisol_data_DryadCortisol data ...